National income and expenditure - "Stone, Richard" (London, 1977)
The Tenth Edition of this basic text for economic studies is designed to give the student a clear, concise picture of the concepts of national income and expenditure and how they fit into an accounting structure of the national economy. In this new edition, opportunity has been taken to update and expand several sections of the text, including matrix presentation of the national accounts which clearly show how the various discrepancies in official estimates are related to each other. There is also a short description on some recent work on accounting for pollution.
Keywords: Income